Unleashing the potential of NOD- and Toll-like agonists as vaccine adjuvants - Maisonneuve, Charles (National Academy of Sciences, 2014)
Innate immunity confers an immediate nonspecific mechanism of microbial recognition through germ line-encoded pattern recognition receptors (PRRs). Of these, Toll-like receptors (TLRs) and nucleotide-binding and oligomerization domain (NOD)-like receptors (NLRs) have shaped our current understanding of innate regulation of adaptive immunity. It is now recognized that PRRs are paramount in instructing an appropriate adaptive immune response. Their ligands have been the focus of adjuvant research with the goal of generating modern vaccine combinations tailored to specific pathogens. In this review we will highlight the recent findings in the field of adjuvant research with a particular focus on the potential of TLR and NLR ligands as adjuvants and their influence on adaptive immune responses.